Omah Halal Activation as an Effort to Strengthen the Halal Ecosystem In Ngronggo Village, Kediri City - Aziza Anggi Maiyanti; Ropingi el Ishaq; Nurlaili Adkhi Rizfa Faiza; Muhammad Fikri Alan (KENDURI : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service aims to activate Omah Halal as an effort to strengthen the community-based halal ecosystem in Ngronggo Village, Kediri City. The service activities are carried out with an Asset-Based Community Development (ABCD) approach that emphasizes the mapping and optimization of local assets, including MSME actors, village institutions, human resources, and academic support. The stages of service include discovery, dream, design, and destiny which are implemented through halal socialization activities, training of Omah Halal managers and Halal Product Process Companions (PPH), as well as halal certification assistance for MSMEs both through self-declare (SEHATI) and regular schemes. The results of the service show that the activation of Omah Halal is able to function as a halal certification service center, halal incubation house, and community halal literacy center. In addition to increasing literacy and access to halal certification for MSMEs, Omah Halal also acts as a cross-sector collaboration node that encourages active community participation and the formation of a sustainable halal living culture at the village level.